The Impact of Demographic and Clinical Factors on the Quality of Life in Patients with Neurodegenerative Cerebellar Ataxias - Olivera Tamaš; Gorica Marić; Milutin Kostić; Andona Milovanović; Katarina Đurđević; Biljana Salak Đokić; Elka Stefanova; Tatjana Pekmezović; Nataša Dragašević-Mišković (Brain Sciences, 2023)
In neurodegenerative cerebellar ataxias, not only ataxia but also extra-cerebellar signs have a significant impact on patients’ health related to quality of life (HRQoL). The aim of this study was to evaluate the various aspects of HRQoL and predictors of QoL in patients with neurodegenerative cerebellar ataxias. We included a total of 107 patients with cerebellar degenerative ataxia. Patients filled out the validated Serbian version of the SF-36 used for the assessment of HRQoL. All patients were clinically evaluated using SARA, INAS, and neuropsychological tests to assess their global cognitive status and different psychiatric scales. The most frequent types of neurodegenerative cerebellar ataxias were autosomal dominant ataxias (38.3%) and sporadic ataxias (32.7%). Mean age at diagnosis was 35.3 ± 16.23 years, and disease duration was on average 12.1 ± 9.91 years. Mean total SF-36 score was 50.63 ± 20.50. Hierarchical regression analysis showed that in the case of the PHC score, the most significant predictors are the patient’s actual age, severity of ataxia, and ACE total score. For MHC, the Hamilton depression score was the most important predictor. Our study has shown that HRQoL measured by SF-36 in patients with neurodegenerative cerebellar disorders is strongly influenced by impaired mobility and depression.